Transient Protection Schemes for Transmission Lines Used in Offshore Wind Farm: A State-of-the-Art Review - Sun, Xiangfei; Yang, Xiao; Cai, Jingfei; Jiang, Xiaohan (Frontiers in Energy Research, 2022)
The weak feeder and high harmonic characteristics of wind farms connected to the grid have an impact on the safe operation of the system, especially on the action selectivity and reliability of the traditional work-frequency quantity protection, which makes the transient protection of wind farm become a hot direction of wind power development and research. In this paper, the key technologies of transient protection for offshore wind farm transmission lines are reviewed, including the analysis of the fault characteristics of wind farm transmission lines based on two types of wind turbines (i.e., doubly-fed asynchronous wind turbines and direct-drive permanent magnet synchronous generators), while the comparison with the characteristics of ground faults and short-circuit faults in traditional synchronous power systems as well as the current status of research on transient protection for offshore wind farm transmission lines, upon which the protection of wind farm transmission lines are also discussed.